A study on the moderating effect of cultural dimensions on job-related diversity and team performance in an Indian automotive industry - P, Niranjani Ruba; Praseeda, C. (International Journal of Psychosocial Rehabilitation, 2020)
In today’s changing business environment, team performance is critical to the survival and having higher impact on the success of the organization. Though, the relevant literature highlights the importance of diversity on team performance, previous studies have mainly focused on demographic and job-related diversity on team performance but not address the moderating effect of cultural dimensions. To address this gap, this study integrates the independent variable as job-related diversity and team performance as dependent variable and examined whether the cultural dimensions are moderated or not. The results of the analysis have demonstrated the effect of job-related diversity on team performance which was moderated by team power distance and team collectivism, such that higher power distance teams and more collectivistic teams exhibited stronger positive effects of job-related diversity on team performance.